A new perspective on the synchronverter model. (September 2022) - Kryonidis, Georgios C.; Malamaki, Kyriaki-Nefeli D.; Mauricio, Juan Manuel; Demoulias, Charis S.
Abstract: In this short communication, a modified version of the well-established synchronverter model is proposed, introducing improved control characteristics that allow the efficient integration of converter-interfaced renewable energy sources to the electrical grid. In the proposed model, the inertial response is decoupled from the primary frequency response. Furthermore, a condition for a critically damped provision of inertial response is proposed. The improved performance of the proposed model against the variants of the synchronverter model is assessed by performing time-domain simulations and stability analysis. Highlights: Control algorithm that decouples inertial response from primary frequency response. Closed-form formula for critically damped provision of inertial response. Improved damping against the current state-of-the-art solutions.